2016
DOI: 10.1002/chem.201602195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aqueous Aerosols in the “Glyoxylate Scenario”: An Experimental Approach

Abstract: The origin of life is one of the fundamental questions in science. Eschenmoser proposed the "glyoxylate scenario", in which plausible abiotic synthesis pathways were suggested to be compatible with the constraints of prebiotic chemistry. In this proposal, the stem compound is HCN. In this work, we explore the "glyoxylate scenario" through several syntheses of HCN polymers, paying particular attention to the role of the aqueous aerosols, together with statistical methods, as a step to elucidate the synthetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 65 publications
(96 reference statements)
2
49
0
Order By: Relevance
“…[14] Recently, 1 was identified in the polymerization of hydrogen cyanide in aqueous solution as proposed by Eschenmoser. [15] Mohammed et al demonstrated the synthesis of glyoxylate in non-enzymatic transamination reactions of 3 and 7 under prebiotic liquid conditions, [16] but these transformations bear only little relevance to reactions in the interstellar medium, where liquid water is unlikely to exist.…”
Section: Dedicated To Drhans Peter Reisenauermentioning
confidence: 99%
“…[14] Recently, 1 was identified in the polymerization of hydrogen cyanide in aqueous solution as proposed by Eschenmoser. [15] Mohammed et al demonstrated the synthesis of glyoxylate in non-enzymatic transamination reactions of 3 and 7 under prebiotic liquid conditions, [16] but these transformations bear only little relevance to reactions in the interstellar medium, where liquid water is unlikely to exist.…”
Section: Dedicated To Drhans Peter Reisenauermentioning
confidence: 99%
“…HCN polymers are mainly known in the fields of prebiotic chemistry, in studies on the origins of life and in astrobiology, because they are considered to play key roles in the formation of the first and primeval protometabolic and informational systems and most stable organics in space . Indeed, HCN polymers may be among the organic macromolecules that are most readily formed in the solar system .…”
Section: Introductionmentioning
confidence: 99%
“…This makes all characterization methods and separation techniques that require solubility impossible, and the water-soluble intermediates of polymerization show ab road distribution of molecular weights and highly charged structures. [4][5][6] HCN polymers are mainly known in the fields of prebiotic chemistry,i ns tudies on the origins of life and in astrobiology, because they are considered to play key roles in the formation of the first and primeval protometabolic and informational systems [7][8][9][10] and most stable organics in space. [11] Indeed,H CN polymers may be among the organic macromolecules that are most readily formed in the solar system.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Both rotamers can be photochemically interconverted with the (E,E)c onformer being enriched through H-tunneling rotamerization. [15] Mohammed et al demonstrated the synthesis of glyoxylate in non-enzymatic transamination reactions of 3 and 7 under prebiotic liquid conditions, [16] but these transformations bear only little relevance to reactions in the interstellar medium, where liquid water is unlikely to exist. Glyoxylic acid has been suggested to form via ultraviolet (UV) exposure of water and acetylene solutions.…”
Section: Dedicated To Drhans Peter Reisenauermentioning
confidence: 99%